L925I mutation in the Para-type sodium channel is associated with pyrethroid resistance in Triatoma infestans from the Gran Chaco region. - Natalia Capriotti; Gastón Mougabure-Cueto; Rolando Rivera-Pomar; Sheila Ons (Public Library of Science (PLoS), 2014)
BACKGROUND: Chagas' disease is an important public health concern in Latin America. Despite intensive vector control efforts using pyrethroid insecticides, the elimination of Triatoma infestans has failed in the Gran Chaco, an ecoregion that extends over Argentina, Paraguay, Bolivia and Brazil. The voltage-gated sodium channel is the target site of pyrethroid insecticides. Point mutations in domain II region of the channel have been implicated in pyrethroid resistance of several insect species. METHODS AND FINDINGS: In the present paper, we identify L925I, a new pyrethroid resistance-conferring mutation in T. infestans. This mutation has been found only in hemipterans. In T. infestans, L925I mutation occurs in a resistant population from the Gran Chaco region and is associated with inefficiency in the control campaigns. We also describe a method to detect L925I mutation in individuals from the field. CONCLUSIONS AND SIGNIFICANCE: The findings have important implications in the implementation of strategies for resistance management and in the rational design of campaigns for the control of Chagas' disease transmission.